Sentinel lymph nodes identification in early breast cancer - peritumoral or subareolar injection of lymphotropic blue dye? - Baichev, George (Radiology and oncology (Ljubljana), 2001)
Background. The sentinel lymph node (SLN) biopsy is a recently developed, minimally invasive method for staging the axilla in patients with early breastcancer. The authors investigated the optimal technique-peritumoral versus subareolar injection for the localization of the SLN. Patients and methods. 192 procedures out of 238 ones were performed using a blue dye peritumoral injection at the early breast cancer site against 46, with a subareolar technique. All patients underwent sentine node biopsy, followed by an axillary node dissection. Results. The SLN were metastatic in 69 out of 80 axillary positive patients that accounted for 86,3%. The sentinel node histology correctly predicted the axillary disease in 90,6% with a peritumoralinjection versus 68,8% with a subareolar lymphatic mapping. Conclusions. This experience indicates that the peritumoral injection of blue dye is a more accurate than the subareolar one for axillary staging.
Keywords: Axilla; Biopsy; breast; Breast neoplasms; diagnostika; dojke; Lymph nodes; Lymphatic metastasis; Neoplasm staging; Pathology; rak (medicina)